2012
DOI: 10.1515/ijamh.2012.016
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of prenatal substance use

Abstract: Because of the long-term consequences of prenatal drug exposure on child and adolescent mental health, health providers need to promote substance use prevention, screen for exposure effects and provide or refer affected youths for intervention services. Preventive measures and treatment should consider other factors that may further increase the risk of psychopathology in the exposed children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
1
32
0
3
Order By: Relevance
“…Negative consequences do not end at birth, with longitudinal studies continuing to find that children and adolescents exposed to drugs in utero are more likely to experience a range of physical and neurodevelopmental problems (63). While negative consequences of heavy drinking during pregnancy such as FAS and FASD are well-known (64), a recent meta-analysis found that even moderate drinking during pregnancy was associated with such childhood problems as trouble following classroom directions, unwillingness to share and impatience while waiting for adult attention (65).…”
Section: Pregnant Women: Special Considerationsmentioning
confidence: 99%
“…Negative consequences do not end at birth, with longitudinal studies continuing to find that children and adolescents exposed to drugs in utero are more likely to experience a range of physical and neurodevelopmental problems (63). While negative consequences of heavy drinking during pregnancy such as FAS and FASD are well-known (64), a recent meta-analysis found that even moderate drinking during pregnancy was associated with such childhood problems as trouble following classroom directions, unwillingness to share and impatience while waiting for adult attention (65).…”
Section: Pregnant Women: Special Considerationsmentioning
confidence: 99%
“…As bleeding in the first trimester is typically caused by hormonal influences, we do not believe in a causal role but a chance finding. Furthermore, no correlation between bleeding and methanol exposure or any other 25 did not list bleeding as a complication but the well-known risks for the developing brain. For cocaine and opiates, lower birth weight was described and additionally premature birth in opiate users.…”
Section: Discussionmentioning
confidence: 96%
“…Sithisarn, Granger, and Bada (2012) conclude that the use of these types of substances by pregnant women represents a “public health problem and social morbidity with consequences on both the users and their children” (p. 105). Demographic covariates, including socioeconomic status, parity, prenatal care, race, and nutrition, often affect the varying degrees of impact that these substances can have on the short- and long-term health of the infant (Minnes, Lang, & Singer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, outcomes are impacted by the combination of drugs used during pregnancy. Many women who use substances are likely to be “polydrug users” (i.e., to use a combination of various substances; Sithisarn et al, 2012). …”
Section: Introductionmentioning
confidence: 99%